The impact of transformational leadership and knowledge management on organizational performance through organizational resilience - Yuki, Narumi; Setyawan, Agustinus (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, Indonesia, 2024)
The quality of a workforce is closely tied to the achievement of organizational goals and overall success. Because of its critical impact on business performance, companies place great emphasis on ensuring high-quality employee performance. This research aims to examine the influence of transformational leadership and knowledge management on organizational performance through organizational resilience. This study uses primary data collected through questionnaires distributed via Google Forms, utilizing a Likert scale for responses. The data analysis was carried out using PLS-SEM method (Partial Least Squares SEM). The results of this study indicate that transformational leadership and knowledge management influence organizational resilience through organizational performance.